2015
DOI: 10.1007/s00604-015-1597-2
|View full text |Cite
|
Sign up to set email alerts
|

Glassy carbon electrode modified with gold nanoparticles and hemoglobin in a chitosan matrix for improved pH-switchable sensing of hydrogen peroxide

Abstract: Hemoglobin (Hb) has been demonstrated to endow electrochemical sensors with pH-switchable response because of the presence of carboxyl and amino groups. Hb was deposited in a chitosan matrix on a glassy carbon electrode (GCE) that was previously coated with clustered gold nanoparticles (Au-NPs) by electrodeposition. The switching behavior is active ("on") to the negatively charged probe [Fe(CN) 63− ] at pH 4.0, but inactive ("off") to the probe at pH 8.0. This switch is fully reversible by simply changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recently, Gu and co-workers reported that Hb, as an important redox respiratory protein in red cells, was coupled with metal NPs such as AuNPs [43] and AgNPs [44] to modify electrodes with remarkable response to different pH solution. For instance, the pH sensitive LBL films were fabricated by alternately adsorbing Hb and conductive AgNPs on the surface of chitosan modified GC electrode.…”
Section: Proteinsmentioning
confidence: 99%
“…Recently, Gu and co-workers reported that Hb, as an important redox respiratory protein in red cells, was coupled with metal NPs such as AuNPs [43] and AgNPs [44] to modify electrodes with remarkable response to different pH solution. For instance, the pH sensitive LBL films were fabricated by alternately adsorbing Hb and conductive AgNPs on the surface of chitosan modified GC electrode.…”
Section: Proteinsmentioning
confidence: 99%